The Mosquers: A network of mosques as education centre - Ahmad Dahlan, Abdul Rahman; Mat Hu, Mohamad Amir; Mohd Ali, Muhammad Hazim; Mohd Bashir, Amirah Hafizah; Norhani, Ain Najla (Eclat Research Publication, 2016)
In this project, as the network of mosques is being used as the center of education in delivering the soft skill values, a mobile application will be developed in order to help the community to gain access to the news related to the soft skill programs. To build a suitable and friendly user application, an interview had been conducted to a different set of users; the orphan, single mother, poor people and also the mosque’s management staff to have their opinion regarding this project. From the result of the interview, some of the important views from the target users had been implemented to the project business model canvas and value proposition design while maintaining some of the important original ideas of the project to create the best and contented business model canvas. This project is hopefully will be able to revive the role of mosque as the center of the education and also help the community to join the program offered with ease by making use of the application.